Predictors of Financial Behavior: Using the Theory of Planned Behaviour - Tharshiga, P. (University of Kelaniya, 2024)
The primary objective of the proposed study is to examine the predictors of financial behaviour in the Northern province of Sri Lanka. Previous studies' results have shown that these predictors are significantly associated with individual financial performance in managing personal finances. In Sri Lankan Context, this study also provides important statistical evidence pointing to a potential future aging population issue, further underscoring the study’s relevance. The Theory of Planned Behavior (TPB) is used by the researcher for their financial context application. The relationship between attitude, subjective norm, perceived behavioural control and intention has been examined in relation to TPB framework, resulting in financial behaviour determinants. This research is therefore novel being the first one theoretically arguing for an expansion of the TPB model starting with financial knowledge in Northern Province, Sri Lanka. The TPB framework forms the foundation for investigating how financial knowledge influences financial behaviour through attitudes toward retirement, subjective norms, and perceived behavioural control, ultimately impacting intention. The researcher believed that the study will provide valuable insight to policymakers, academic groups, and practitioners. Additionally, by raising awareness about finance and retirement, the study is expected to offer meaningful contributions to society. The researchers also recommend that similar studies using these proxies should be conducted in other regions to expand the understanding of financial behavior.
Keywords: Financial behaviour; Financial Knowledge; Retirement planning; Subjective Norms; Theory of planned behaviour